STUDI PENGENDALIAN PERSEDIAAN BAHAN BAKU BERAS (Kasus di PT. Buyung Putra Pangan PP Buyung Kabupaten Banyuasin) Study inventories control of rice s raw material (Case in Buyung Putra Pangan Ltd. PP Buyung Banyuasin Regency) - Saputra, Andrik; H. Anang, Rahidin; Iswarini, Harniatun (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT This research aims to study of inventories contol of rice raw materials at Buyung Putra Pangan Ltd. PP Buyung Banyuasin Regency and to examine the problems in inventories of rice raw materials at Buyung Putra Pangan Ltd. PP Buyung Banyuasin Regency. This research has been conducted at Buyung Putra Pangan Ltd. PP Buyung Banyuasin Regency, time data taking over conducted in May – July 2017. The research method used was the case study method, the sample method used was the purposive sampling, collection data method used is the observation, interviews and documentation. Process method and analysis data used to answer the problem first and second is a qualitative-descriptive, to know the princely safety stock using the formula safety. Our results indicate that of inventories control of rice raw material at Buyung Putra Pangan Ltd. PP Buyung Banyuasin Regency use by way to perform, own production to need meet raw material as long production, to perform to do stock rice the Silo GSI used was the formula safety stock in the amount of 6,596.27 tons every month of rice raw material available permanent. And obstacles faced by trade in inventories rice raw material is no yet available raw material to do collectors every time and great less kapacitas stock the raw material (Rice Silo GSI).